The heritage of the Nuremberg tribunal - Jovašević Dragan (Zbornik Radova Pravnog Fakulteta u Nišu, 2015)
As a system of legal rules contained in the documents of the international community and in the national (internal) criminal legislation, the International Criminal Law envisages the criminal liability and punishment for a vast number of international crimes. These criminal acts imply a violation of laws of war and customs of warfare (the International Humanitarian Law) as well as the acts of disturbing or endangering peace among nations and the security of mankind. The contemporary International Criminal Law envisages the most severe forms of punishment and penal measures for these criminal offences. The perpetrators of these crimes are, in certain cases, subject to the primary jurisdiction of one of international criminal court (supranational) authorities, such as the International Military Tribunal at Nuremberg. In this paper, the author analyzes the importance of the Nuremberg court for the development of international criminal law, including the notion and characteristics of international crimes and the principles of criminal liability.